Evaluating Retention of Onlay Versus Complete Coverage Using E.Max-Restoration - Sireen Meheshi,; Enas Khamakhim, (AlQalam Journal of Medical and Applied Sciences, 2024)
This study compared the retention of different types of indirect restorations (only or full coverage) utilized on endodontically treated molars. Fourteen patients requiring restoration of endodontically treated molars were randomly allocated into two groups (n = 7) according to the type of restoration used. lithium disilicate ceramic crowns were given to the control group. While lithium disilicate ceramic onlays were given to the intervention group. The heat pressing technique was used for the fabrication of both restorations. Following the final cementation with adhesive resin cement, the restoration was assessed at three, six, twelve, and twenty-four months using the modified USPHS criteria. Statistical analysis was performed using the chi-square test. Results: At all intervals, there was no statistically significant difference in retention (P > 0.05) between the two tested groups. Both groups showed comparable results, with full coverage showing somewhat higher retention after 2 years. Regardless of the type of restoration, the emax-press produced high clinical performance in terms of retention. Compared to full coverage, onlay has proven to be a trustworthy substitute.